Endometriosis With Regenerative Skeletal Muscle Cells In The Abdominal Wall After Cesarean Section: A Case Report - Astari, Prilly; Susanto, Ricky; Tjandra, Ong; Wongkar, Fresia Juwitasari (Sean Institute, 2024)
Endometriosis in the abdominal wall following a caesarean section is an uncommon occurrence, accounting for only 0.03%- 1.5%. Diagnosis is often late, so symptoms become more severe or the mass size increases. Delayed diagnosis increases morbidity, complications, and the complexity of treatment to reduce symptoms and remove the endometriosis mass. We report a 33-year-old female patient with a mass in the anterior abdominal wall that appeared over the past two months. The patient experienced mass enlargement and cyclic pain which began three days before menstruation. The patient had a history of one cesarean section and did not use contraception. Ultrasonography examination showed a mixechoic image of the anterior abdominal wall of the cesarean section scar measuring 2.48 x 2.45 x 1.38 cm. We performed a wide excision up to 1 cm outside the mass. Pathological anatomy showed endometrial glands and stroma between skeletal muscle tissue that were consistent with external endometriosis with regenerative skeletal muscle cells. Understanding the histology and immunohistochemistry of muscle cell regeneration, as well as basic clinical examination, is very helpful in establishing a diagnosis so that appropriate management can be carried out.